STRATEGI PEMERINTAH KOTA DUMAI DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) MELALUI PERUSAHAAN DAERAH (PD) PELABUHAN DUMAI BERSEMAI TAHUN 2005 - 2010. - RANNUH WIJAYA PUTRA; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Strategy Of Increasing Local Revenues (PAD) is interesting to study because an important factor in the implementation of regional autonomy as one of the government's success in organizing the financial management area. This study describe’s the government's strategy to increase revenue through local companies PD. Pelabuhan Dumai Bersemai.This study used a qualitative method and conducted in Dumai city. This study uses informants as sources of information objects that aims to achieve mastery in getting information. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants. Analysis of the data in a descriptive study conducted by describing the data in a systematic and objective so as to produce factual information, current, and accurate.Based on the results of the study found the following matters : first, PAD Improvement Strategy in PD. Pelabuhan Dumai Bersemai have a strategy that in cludes: Optimization of Corporate Strategy, Corporate Business Recovery Strategy, Potential Restructuring Company. The implementation of recovery strategies see the number of requests and restructuring loans made PD. Pelabuhan Dumai Bersemai and Local Government, to prepared anticipation government strategy in the management of the port as a benchmark for successful implementation of the strategy of empowering PD. Pelabuhan Dumai Bersemai. Second, as for one of the factors that influence the increase inrevenuein PD. Pelabuhan Dumai Bersemai is the capital of the Government and also the expansion of the port area by a third party to improve service eassets, and the increase in the number of ship visit severy year.Keyword: Strategy, IncreasingLocal Revenues(PAD), Dumai.